WORK-LIFE BALANCE AND EMPLOYEE COMPETENCE AND ITS INFLUENCE ON EMPLOYEE PERFORMANCE AT BANK JATIM LAMONGAN THROUGH WORK MOTIVATION - Hariati, Wiwik; Sunaryo, Hadi; Salim, M. Agus (International Journal of Cultural and Social Science, 2025)
In an era of increasing business competition and dynamic digital transformation, employee performance becomes a crucial factor for the success of banking institutions such as Bank Jatim Lamongan. Work-life balance and employee competence are two important aspects that can influence this performance. Additionally, work motivation acts as a key driver in enhancing employee productivity and effectiveness. Therefore, this study aims to examine the influence of work-life balance and employee competence on employee performance, with work motivation as a mediating variable. The research object is the employees of Bank Jatim Lamongan branch. The approach used is quantitative with explanatory research methods, where data were collected through research instruments and analyzed statistically to test the relationships between variables. The results show that employee competence and work motivation have a significant positive effect on performance, while work-life balance only affects work motivation and does not directly impact employee performance. These findings emphasize the importance of managing competence and motivation to improve employee performance in the banking environment.